Impact assessment : practical solutions to recurrent problems and contemporary challenges - Lawrence, David P. (David Phillip), 1947-; Lawrence, David P. (David Phillip), 1947- (Hoboken, N.J. : Wiley, 2013)
Taking a problem-oriented approach, Environmental Impact Assessment provides an in-depth, practical, and comprehensive guide for designing and implementing effective Environmental Impact Assessment (EIA) processes. Easily adaptable for application in other jurisdictions, this thoroughly updated second edition addresses a much broader range of practice-related problems, issues, and challenges in EIA. The text also includes a new set of practice-based stories to provide a real-world context for the conceptual and applied analyses. End-of-chapter checklists provide a handy tool for structu.
Introduction -- Conventional IA Processes -- How To Make IAs More Influential -- How To Make IAs More Rigorous -- How To Make IAs More Rational -- How To Make IAs More Substantive -- How To Make IAs More Practical -- How To Make IAs More Democratic -- How To Make IAs More Collaborative -- How To Make IAs More Ethical -- How To Make IAs More Adaptive -- How To Connect and Combine IA Processes.
Revised edition of: Environmental impact assessment. Published: Hoboken, New Jersey : Wiley-Interscience, 2003.
"Published simultaneously in Canada"--Title page verso.
Includes bibliographical references (pages 435-468) and index.
Online resource; title from PDF title page (Wiley, viewed July 10, 2013).
Keywords: Environmental impact analysis; Environmental impact analysis; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; NATURE -- Natural Resources; Environmental impact analysis; Milieueffecten; Milieuverontreiniging; Milieuaantasting; Electronic books